1990
DOI: 10.1021/bi00460a004
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of apocytochrome b5: presence of a stable native core

Abstract: Upon removal of the heme group, the water-soluble fragment of cytochrome b5 adopts a conformation less stable and compact than that of the holoprotein [Huntley, T. E., & Strittmatter, P. (1972) J. Biol. Chem. 247, 4641-4647]. This conformation, imposed by the amino acid sequence alone, has not been described in detail. One- and two-dimensional proton nuclear magnetic resonance spectroscopy techniques were applied to the apoprotein of the soluble fragment of rat liver cytochrome b5 in an effort to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
5
54
0
1
Order By: Relevance
“…Furthermore, on the tryptic fragment it was shown by NMR (Moore & Lecomte, 1990Moore et al, 1991) that apocytochrome b5 has a hydrophobic core region. Current interest is focused on protein folding concerns, in particular the stage at which intermediates occur that are able to undergo a cooperative transition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, on the tryptic fragment it was shown by NMR (Moore & Lecomte, 1990Moore et al, 1991) that apocytochrome b5 has a hydrophobic core region. Current interest is focused on protein folding concerns, in particular the stage at which intermediates occur that are able to undergo a cooperative transition.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results of many workers indicate that aromatic residues may be important in the formation of "islands" of stable structure in partially folded and/or nonnative states (Moore & LeComte, 1990). Regions of cytochrome c showing the highest protection factors in the acid-denatured A form are those that contribute to the hydrophobic core of the native protein and contain several aromatic side chains (Jeng et al, 1990).…”
Section: Potential Applicability Of Msp Data To Protein Foldingmentioning
confidence: 99%
“…The covalently bound porphyrin plays an integral role in cyt c folding, possibly as a hydrophobic nucleation site, but does not lead to nonnative clusters and misfolded traps (10). Many b-type cytochromes (e.g., cyt b 5 and cyt b 562 ), however, adopt native or near-native structures in the absence of their noncovalently bound porphyrins (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the basis of these observations, it has been suggested that folding precedes heme incorporation in the b-type cytochromes, whereas heme attachment is a prerequisite for folding in the c-type proteins.…”
mentioning
confidence: 99%